Timed Bromocriptine-QR Therapy Reduces Progression of Cardiovascular Disease and Dysglycemia in Subjects with Well-Controlled Type 2 Diabetes Mellitus - Bindu Chamarthi; J. Michael Gaziano; Lawrence Blonde; Aaron Vinik; Richard E. Scranton; Michael Ezrokhi; Dean Rutty; Anthony H. Cincotta (Journal of Diabetes Research)
Background. Type 2 diabetes (T2DM) patients, including those in good glycemic control, have an increased risk of cardiovascular disease (CVD). Maintaining good glycemic control may reduce long-term CVD risk. However, other risk factors such as elevated vascular sympathetic tone and/or endothelial dysfunction may be stronger potentiators of CVD. This study evaluated the impact of bromocriptine-QR, a sympatholytic dopamine D2 receptor agonist, on progression of metabolic disease and CVD in T2DM subjects in good glycemic control (HbA1c ≤7.0%). Methods. 1834 subjects (1219 bromocriptine-QR; 615 placebo) with baseline HbA1c ≤7.0% derived from the Cycloset Safety Trial (this trial is registered with ClinicalTrials.gov Identifier: NCT00377676), a 12-month, randomized, multicenter, placebo-controlled, double-blind study in T2DM, were evaluated. Treatment impact upon a prespecified composite CVD endpoint (first myocardial infarction, stroke, coronary revascularization, or hospitalization for angina/congestive heart failure) and the odds of losing glycemic control (HbA1c >7.0% after 52 weeks of therapy) were determined. Results. Bromocriptine-QR reduced the CVD endpoint by 48% (intention-to-treat; HR: 0.52 [0.28−0.98]) and 52% (on-treatment analysis; HR: 0.48 [0.24−0.95]). Bromocriptine-QR also reduced the odds of both losing glycemic control (OR: 0.63 (0.47−0.85), p=0.002) and requiring treatment intensification to maintain HbA1c ≤7.0% (OR: 0.46 (0.31−0.69), p=0.0002). Conclusions. Bromocriptine-QR therapy slowed the progression of CVD and metabolic disease in T2DM subjects in good glycemic control.